Treatment of microcystin-LR cyanotoxin contaminated water using Kentucky bluegrass-derived biochar. (June 2021) - Song, Hak Jin; Gurav, Ranjit; Bhatia, Shashi Kant; Lee, Eun Bin; Kim, Hyung Joo; Yang, Yung-Hun; Kan, Eunsung; Kim, Ho Hyun; Lee, Sang Hyun; Choi, Yong-Keun
Graphical abstract: Highlights: Biochar was prepared from various waste biomass at different pyrolytic temperature. Kentucky bluegrass-derived biochar was the best for microcystin-LR adsorption. Selected biochar revealed maximum adsorption capacity of 2769 μg MC g −1 BC. Adsorption of microcystin-LR followed Elovich, and Freundlich models. Metal ions in real wastewater interfered the adsorption of microcystin-LR to biochar. Abstract: The present study revealed adsorption behaviors of microcystin-LR (MC-LR) on pristine biochars (BCs) derived from various waste biomass of Kentucky bluegrass (KB) ( Poa pratensis L.), microalgae ( Spirulina sp.), grape pomace, coffee residues, and rice husk. BCs obtained from waste biomass on pyrolysis at 350, 550, and 750 °C for 2 h demonstrated different physicochemical characteristics. The maximum adsorption capacity of 2769 μg MC-LR/g was observed in KB biochar prepared at 750 °C (KB-BC750) with the involvement of hydrophobic and π-π interaction, electrostatic attraction, ion exchange, and surface complexation as the principal adsorption mechanisms. MC-LR adsorption onto KB- fitted well to Elovich kinetic and Freundlich isotherm model or the sorption. Furthermore, MC-LR adsorption from the real wastewater using KB-BC750 demonstrated significant removal (ca. 50 %) as compared to the distilled water. Therefore, the results of the present study have heightened the strategies to remove MC-LR from the wastewater using cheap adsorbents like KB-BCs.